Analysis of Hormones and Coccidiostats in Dust from Animal Husbandry - Pauelsen, Frances; Justus Liebig University Giessen (My University, 2026)
The growth of the global population is accompanied by an increasing consumption of animal-derived food products. To meet this steadily growing demand, hormones, coccidiostats and other veterinary pharmaceuticals are employed to enhance the efficiency and profitability of breeding and fattening facilities while ensuring a certain level of animal welfare. The use of various veterinary pharmaceuticals leads to environmental contamination via multiple exposure pathways. Whilst the primary routes of entry via manure and slurry are well established, stable dust has hitherto received little consideration as a potential exposure pathway. This dissertation systematically investigates the occurrence of steroid hormones (oestrogens, androgens, and progestogens) and coccidiostats (ionophores and synthetic compounds) in stable dust from various animal husbandry facilities using liquid chromatography–tandem mass spectrometry (LC-MS/MS). A novel LC-MS/MS method was developed for the analysis of stable dust samples and fully validated according to Commission Implementing Regulation (EU) 2021/808, enabling the detection of 22 steroids and coccidiostats at trace analytical concentrations in complex matrices. Extraction parameters were optimised and validated through systematic optimisation experiments (Design of Experiments). For 17 of the 22 analytes, specificity, selectivity, and uncertainty related performance characteristics of the method comply with international requirements for residues in foodstuffs. Analysis of 50 stable dust samples from laying hen facilities, broiler chicken operations and breeding sow facilities revealed coccidiostat concentrations in the mg/kg range (e.g. narasin up to 15.72 mg/kg, nicarbazin up to 11.50 mg/kg) and steroid hormone levels ranging from 0.30–2.62 mg/kg in some instances. Archive samples from the 1980s demonstrate the persistence of these substances over decades. A risk assessment using PEC/PNEC ratios for aquatic organisms indicates an elevated environmental risk. The results provide further indications that stable dust represents a previously underestimated environmental and exposure compartment. Sub-therapeutic doses of coccidiostats in dust particles may promote the development of resistant parasite strains. The inhalation of dust contaminated with various pharmaceutical residues moreover may presents a previously underestimated occupational health risk. This work contributes substantially to the understanding of a novel entry route of veterinary pharmaceuticals and feed additives into the environment and provides a scientific foundation for future hygiene and occupational safety measures in intensive animal husbandry within the context of the One Health Approach.
Keywords: Hormones; Coccidiostats; Animal Husbandry; LC-MS/MS; ddc:570; ddc:540